Employee Perceptions of Work-Life Balance and Its Implications for Decision-Making and Performance: A Study at PT Roti Dewi Bandung in Mbawi Village, Dompu Regency - Sri Kurniati; Muh. Syahru Ramadhan; Desi Rubiyanti (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to explore employees’ perceptions of work-life balance and its implications for decision-making and performance at PT Roti Dewi Bandung. The research employed a descriptive qualitative approach using semi-structured interviews with three key informants. The results indicate that work-life balance is not yet optimal due to high workloads, long working hours, and limited flexibility. This imbalance negatively affects decision-making leading to hasty and unfocused actions and decreases performance due to fatigue and emotional strain. Although the company provides support such as leave flexibility, it is insufficient to ensure a holistic balance. This study contributes to understanding work-life dynamics in small rural enterprises and suggests more humane and adaptive workplace policy reforms.